RIN2 syndrome: Expanding the clinical phenotype. Issue 9 (8th June 2016) - Rosato, Simonetta; Syx, Delfien; Ivanovski, Ivan; Pollazzon, Marzia; Santodirocco, Daniela; De Marco, Loredana; Beltrami, Marina; Callewaert, Bert; Garavelli, Livia; Malfait, Fransiska
Abstract : Biallelic defects in the RIN2 gene, encoding the Ras and Rab interactor 2 protein, are associated with a rare autosomal recessive connective tissue disorder, with only nine patients from four independent families reported to date. The condition was initially termed MACS syndrome (macrocephaly, alopecia, cutis laxa, and scoliosis), based on the clinical features of the first identified family; however, with the expansion of the clinical phenotype in additional families, it was subsequently coined RIN2 syndrome. Hallmark features of this condition include dysmorphic facial features with striking, progressive facial coarsening, sparse hair, normal to enlarged occipitofrontal circumference, soft redundant and/or hyperextensible skin, and scoliosis. Patients with RIN2 syndrome present phenotypic overlap with other conditions, including EDS (especially the dermatosparaxis and kyphoscoliosis subtypes). Here, we describe a 10th patient, the first patient of Caucasian origin and the oldest reported patient so far, who harbors the previously identified homozygous RIN2 mutation c.1878dupC (p. (Ile627Hisfs*7)). Besides the hallmark features, this patient also presents problems not previously associated with RIN2 syndrome, including cervical vertebral fusion, mild hearing loss, and colonic fibrosis. We provide an overview of the clinical findings in all reported patients with RIN2 mutations and summarize some of the possible pathogenic mechanisms that may underlie this condition. © 2016 Wiley Periodicals, Inc.